Influence of tetramethylammonium hydroxide on methane and carbon dioxide gas hydrate phase equilibrium conditions - Khan, M.S. (Elsevier B.V., 2017)
In this experimental work, the phase boundaries of TMAOH + H2O + CH4 and TMAOH + H2O + CO2 hydrates are measured at different concentrations of aqueous TMAOH solution. The temperature-cycle (T-cycle) method is applied to measure the hydrate equilibrium temperature of TMAOH + H2O + CH4 and TMAOH + H2O + CO2 systems within the ranges of 3.5–8.0 MPa and 1.8–4.2 MPa, respectively. Results reveals that, TMAOH acts as a thermodynamic inhibitor for both gases. In the presence of 10 wt of TMAOH, the inhibition effect appears to be very substantial for CO2 with an average suppression temperature (ΔŦ) of 2.24 K. An ample inhibition influence is observed for CH4 hydrate at 10 wt with ΔŦ of 1.52 K. The inhibition effect of TMAOH is observed to increase with increasing TMAOH concentration. Confirmed via COSMO-RS analysis, the TMAOH inhibition effect is due to its hydrogen bonding affinity for water molecules. Furthermore, the calculated hydrate dissociation enthalpies in both systems revealed that TMAOH does not participate in the hydrate crystalline structure. © 2017 Elsevier B.V.